Economic organizations and corporate governance in Japan : - Milhaupt, Curtis J. (Oxford University Press, 2004)
Using an institutional and empirical approach, this book analyses the role of formal rules (law and regulations) and informal rules (norms, practices, and shared beliefs) in the Japanese economy. Through in-depth studies of corporate governance and finance, mergers and acquisitions, financialregulation, and markets for everything from venture capital to legal talent and organized crime, Milhaupt and West show that institutions play a crucial and heretofore overlooked role in the structure of the Japanese economy, which often is portrayed as being governed exclusively by interpersonalrelations and bureaucratic fiat. The book demonstrates that despite outward appearances of a decade of stagnation in Japan, the formal and informal rules of the Japanese economy are changing significantly. The evidence suggests that in the mix of formal and informal rules that govern Japanese firms and set the incentive structurefor other economic actors, law is gaining in importance. As these rules change, Japanese actors are responding, reshaping corporate governance and financial markets, eroding the bureaucracy's power. This book's emphasis on the centrality of institutions, institutional change, and responses to change portray a Japanese economy far different from those provided by previous accounts. It provides a wealth of previously unexplored data on the Japanese economy and legal system, and demonstrates theimportance of a sound incentive roadmap for Japan's economic recovery and transition.